Gain enhancement of microstrip patch antenna using artificial magnetic conductor - Norfatihah Bahari; Mohd Faizal Jamlos; Muammar Mohamad Isa (Institute of Advanced Engineering and Science, 2019)
The paper presents an artificial magnetic conductor (AMC) structure to enhance the gain of the double microstrip patch antenna. By placing this kind of metamaterial in between the two Rogers RT5880 substrates, the antenna achieved lots of improvement especially in terms of size miniaturization, bandwidth, return loss, gain and efficiency. The antenna is intended to operate at 16 GHz where the prospect fifth generation (5G) spectrum might be located. Integration of AMC structure into the proposed antenna helps to improve nearly 16.3% of gain and almost 23.6% of size reduction.